2020
DOI: 10.1097/mrm.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Revival of older antibiotics for the therapy of urinary tract infections: old, but gold Part 1: Antimicrobial susceptibility of extended-spectrum β-lactamase-producing and AmpC β-lactamase-producing Escherichia coli isolates

Abstract: The most prevalent causative agent of urinary tract infections (UTIs) is uropathogenic Escherichia coli, corresponding to 50-90% of uncomplicated, around 30-70% of nosocomial UTIs. There has been renewed interest toward the clinical value of older, nonb-lactam antibiotics (including fosfomycin, nitrofurantoin, trimethoprim/sulfamethoxazole) used for the therapy UTIs caused by drug resistant bacteria, including AmpCproducing or an extended-spectrum b-lactamases (ESBL)-producing Gram-negative strains. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…This finding was consistent with other studies that reported nitrofurantoin presented the lowest resistance and trimethoprim–sulfamethoxazole produced the highest. 13 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding was consistent with other studies that reported nitrofurantoin presented the lowest resistance and trimethoprim–sulfamethoxazole produced the highest. 13 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Resistance development in common UTI pathogens (especially to fosfomycin, sulfamethoxazole-trimethoprim, fluoroquinolones, and third-generation cephalosporins), have seriously restricted therapeutic options, especially in outpatient settings. 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In real clinical practice, this tendency is much clear, and clinicians are experiencing cases of improvement with oral conversion to TMP/SMX. 16 TMP/ SMX is available in oral form and can be used in UTIs caused by ESBL-producing bacteria, which are susceptible to it. The aim of this study was to obtain evidence that TMP/SMX therapy (initial or step-down) is comparable to the ertapenem treatment for ESBL-positive TMP/SMXsensitive Enterobacteriaceae.…”
Section: Introductionmentioning
confidence: 99%